Using ground penetrating radar, scanning electron microscopy and thermal infrared imagery to document near-surface hydrological changes in the old faithful Geyser area, Yellowstone National Park, U.S.A. (July 2017) - Lynne, Bridget Y.; Heasler, Henry; Jaworowski, Cheryl; Foley, Duncan; Smith, Isaac J.; Smith, Gary J.; Sahdarani, Dyah
Highlights: Changes in the shallow subsurface hydrology in the Old Faithful Geyser Area are documented using GPR, SEM, and TIR. Sinter from (1) unaltered terraces, (2) partially-altered terraces, (3) highly-altered terraces were analysed. The alteration is driven by acidic steam condensate overprinting the sinter to various degrees. This subsurface process has resulted in the formation of subsidence bowls in the Old Faithful Geyser Area. Abstract: Ground penetrating radar (GPR), thermal infrared imagery (TIR), scanning electron microscopy (SEM), and X-ray diffraction (XRD) provide an understanding of shallow subsurface altered zones in the Old Faithful Geyser area. The GPR and TIR are temporal snapshots of the hydrothermal system; GPR reflections suggest extensive subsurface zones of hydrothermal alteration. SEM-XRD document changes in hydrologic conditions. SEM-XRD analyses of sinters demonstrate a multi-stage formation history, pH-temperature hydrodynamic changes, and dissolution by acidic steam condensate. TIR images show surface thermal trends that are consistent with mapped fractures and/or faults and with the GPR, SEM and XRD results.